THE IMPACT OF DEMOGRAPHIC FACTORS ON TAX COMPLIANCE IN INDONESIA - Ganda Frisno Pasaribu; Christine Tjen (Universitas Airlangga, 2016)
This study aims to determine how the impact of demographic factors on tax compliance behavior. Tax compliance behavior is seen from the taxpayer's intention to carry out tax evasion. Data was collected by distributing questionnaires and the number of samples was 304 respondents. The results of this study indicate that male and female respondents have the same tax compliance. The results also show that there is no difference in tax compliance between married and unmarried respondents. The independent variables of education level, type of work and income level were significantly correlated with tax compliance.